2014
DOI: 10.1007/s00339-014-8645-3
|View full text |Cite
|
Sign up to set email alerts
|

Micro-fading spectrometry: investigating the wavelength specificity of fading

Abstract: A modified microfading spectrometer incorporating a linear variable filter is used to investigate the wavelength dependence of fading of traditional watercolour pigments, dosimeters and fading standards at a higher spectral resolution and/or sampling than had previously been attempted. While the wavelength dependence of photochemical damage was largely found to correlate well with the absorption spectra of each material, exceptions were found in the case of Prussian blue and Prussian green pigments (the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…The behaviour of these samples was the same as Prussian blue in all cases, and the same conclusions could be drawn as for Prussian blue; a conclusion mirrored in other aspects of this research (Lerwill et al, 2013). There was little other colour change to indicate the behaviour of the (unidentified) yellow components.…”
Section: Prussian Greensupporting
confidence: 82%
“…The behaviour of these samples was the same as Prussian blue in all cases, and the same conclusions could be drawn as for Prussian blue; a conclusion mirrored in other aspects of this research (Lerwill et al, 2013). There was little other colour change to indicate the behaviour of the (unidentified) yellow components.…”
Section: Prussian Greensupporting
confidence: 82%
“…Photo-degradation reduces with wavelength since these materials are more transparent at longer wavelength [6]. Using the results from light-induced accelerated ageing experiments using broadband sources with an approximate daylight spectrum (400-700 nm) of some of the most sensitive pigments such as Prussian blue [16], we can deduce that an OCT operating at 1 mW over a spot size of 17 μm in diameter with an exposure time of 6 μs is at least 4 orders of magnitude below the damage threshold even if the OCT uses a source with the same visible spectrum. Figure 4 shows an example of an application to paint imaging using a mock-up historical paint sample.…”
Section: Fdoct Imaging Of Paint Samples At 2 Micronsmentioning
confidence: 99%
“…Furthermore, Lerwill et al . have recently reported on the wavelength dependence of the fading of traditional watercolour pigments using MFT. In addition, Beltran et al .…”
Section: Methodsmentioning
confidence: 99%
“…The proposed methodology has been successfully applied when performing microfading tests of ethnographic objects [10], natural history collections [16] and Japanese woodblock prints [17], among others. Furthermore, Lerwill et al [18] have recently reported on the wavelength dependence of the fading of traditional watercolour pigments using MFT. In addition, Beltran et al [19] have employed MFT to study cultural heritage materials under anoxic or hypoxic conditions through glazing.…”
Section: Evaluation Of Mft Datamentioning
confidence: 99%